2016
DOI: 10.1530/rep-16-0397
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the bovine oviductal fluid proteome

Abstract: Our objective was to investigate the regulation of the proteome in the bovine oviductal fluid according to the stage of the oestrous cycle, to the side relative to ovulation and to local concentrations of steroid hormones. Luminal fluid samples from both oviducts were collected at four stages of the oestrous cycle: pre-ovulatory (Pre-ov), post-ovulatory (Post-ov), and mid- and late luteal phases from adult cyclic cows (18-25 cows/stage). The proteomes were assessed by nanoLC-MS/MS and quantified by label-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 58 publications
11
81
2
Order By: Relevance
“…The oviduct is a convoluted tube consisting of longitudinal and circular muscular, and a stromal layer lined by a simple cuboidal to columnar epithelium containing both ciliated and secretory cells 83,106,123. The ciliated cells are important for gamete transport and sperm interaction, in particular helping to create a ‘sperm reservoir’; while the secretory cells are responsible for producing oviduct fluid; a mixture of specific cell secretions and serum transudate 1,2,10,63,118. In adult mammals (including the woman), four anatomical segments can be distinguished along the length of the oviduct; the infundibulum, ampulla, isthmus and utero-tubal junction, respectively11,122 (Fig.…”
Section: The Oviductmentioning
confidence: 99%
“…The oviduct is a convoluted tube consisting of longitudinal and circular muscular, and a stromal layer lined by a simple cuboidal to columnar epithelium containing both ciliated and secretory cells 83,106,123. The ciliated cells are important for gamete transport and sperm interaction, in particular helping to create a ‘sperm reservoir’; while the secretory cells are responsible for producing oviduct fluid; a mixture of specific cell secretions and serum transudate 1,2,10,63,118. In adult mammals (including the woman), four anatomical segments can be distinguished along the length of the oviduct; the infundibulum, ampulla, isthmus and utero-tubal junction, respectively11,122 (Fig.…”
Section: The Oviductmentioning
confidence: 99%
“…Changes in the abundance of diverse immunity proteins, such as CD109 and members of the S100 family, were also induced by insemination. CD109 is a cell surface glycoprotein and was also previously detected in the bovine ODF . CD109 can be processed by furin, and the soluble form is involved in TGF‐β signaling .…”
Section: Discussionmentioning
confidence: 91%
“…CD109 is a cell surface glycoprotein and was also previously detected in the bovine ODF. [21] CD109 can be processed by furin, and the soluble form is involved in TGF-β signaling. [73,74] Accordingly, this molecule might be involved in cell signaling events in the rabbit oviduct upon insemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the oviductal proteome changes with the different stages of the oestrous cycle (Lamy et al 2016; Soleilhavoup et al 2016), the presence of gametes (Georgiou et al 2005) or the presence of embryos (Smits et al 2017). The proteome of the oviduct epithelial cells has also been studied in humans (Wang et al 2016) and pigs (Seytanoglu et al 2008).…”
Section: Introductionmentioning
confidence: 99%